Real textile industrial wastewater treatment and biodiesel production using microalgae. (October 2022) - Javed, Fahed; Rehman, Fahad; Khan, Asad Ullah; Fazal, Tahir; Hafeez, Ainy; Rashid, Naim
Abstract: Microalgae are promising feedstocks capable to simultaneously treat wastewater and produce biodiesel. The focus current studyis the treatment of real textile wastewater (RTWW) and successive biodiesel production using microalgae ( Chlorella vulgaris ). Cultivation was carried out in unsterilized 100% (without dilution) and diluted (25%, 50%, 75%) RTWW. Microalgae cultivation in defined media (BG-11) was set as a control. In results, 50% dilution showed the highest decolorization efficiency (99 ± 0.13%), COD removal (82%), and Fatty Acid Methyl Esters (FAMEs) content (32.62 mg g −1 of biomass). Cultivation was carried out in mixotrophic and heterotrophic conditions to improve microalgae performance. Mixotrophic cultivation showed 99 ± 0.29% decolorization, 94% COD removal, and 61.65 mg g −1 of biomass as FAMEs, which was higher (p < 0.05) than the heterotrophic condition. FAME content and COD removal in mixotrophic conditions were higher (p < 0.05) than in photo-autotrophic conditions; however, there was no significant difference (p > 0.05) in the decolorization efficiency. Thus, it turned out that 50% diluted RTWW under mixotrophic conditions was the most suitable choice to achieve high treatment performance and the FAMEs yield. This study demonstrates that RTWW could be used as a microalgae feedstock without sterilization and less freshwater addition (50% of RTWW). Thus, it can be considered a promising feedstock for economical biodiesel production. Graphical abstract: Image 1 Highlights: Microalgae cultivated in un-sterilized real textile wastewater (RTWW). 50% dilution showed the best decolonization efficiency, COD removal, and biodiesel yield. RTWW treatment investigated under auto-trophic, heterotrophic, and mixotrophic conditions. Mixotrophic cultivation showed the highest biomass productivity, COD removal, and biodiesel yield. Mixotrophic cultivation with 50% diluted RTWW turned out as the most suitable choice.